Development of E-Learning Based PBL-STEM Learning Tools on Students' Science Process Skills and Critical Thinking Ability - Kusumawati Dwiningsih; Sukarmin Sukarmin; Achmad Lutfi; Rusly Hidayah; Suyono Suyono; Utiya Azizah; Aiza Alya (Postgraduate, University of Mataram, 2024)
Education in the 21st century must be in harmony with technological developments where students are expected to be able to master useful skills to be responsive to changes and developments over time and to have in-depth knowledge and understanding to become lifelong learners. Based on these problems, the researcher aims to produce e-learning based PBL-STEM learning tools that are valid, practical and effective. This research procedure follows the Borg and Gall research and development method. Where the research method is pre-experimental, researchers use the One Group Pretest - Posttest Design approach. The results of this research are: the teaching tools were declared valid in terms of validation results of 95%, the practicality of the teaching tools seen from the student response questionnaire obtained a score of 95% and the student activity observation sheet as supporting data obtained a value of 98%, and the effectiveness of interactive e-modules can be seen from the average N-Gain value of the science process skills test obtained an average N-Gain value of 0.73 and in the critical thinking ability test obtained an average N-Gain score of 0.70 so it can be concluded that the teaching tools developed are suitable use in learning.